The Future Internet: Future Internet Assembly 2011: Achievements and Technological Promises - Domingue, John (Lecture Notes in Computer Science, 2011)
Computer Communication Networks; Information Systems Applications (incl. Internet); Information Storage and Retrieval; Multimedia Information Systems; Communications Engineering, Networks; Computers and Society